Myeloid Protease-Activated Receptor-2 Contributes to Influenza A Virus Pathology in Mice - Gunther, Randall C.; Bharathi, Vanthana; Miles, Stephen D.; Tumey, Lauryn R.; Schmedes, Clare M.; Tatsumi, Kohei; Bridges, Meagan D.; Martinez, David; Montgomery, Stephanie A.; Beck, Melinda A.; Camerer, Eric; Mackman, Nigel; et al. (Frontiers in Immunology, 2021)
Background: Innate immune responses to influenza A virus (IAV) infection are initiated in part by toll-like receptor 3 (TLR3). TLR3-dependent signaling induces an antiviral immune response and an NFκB-dependent inflammatory response. Protease-activated receptor 2 (PAR2) inhibits the antiviral response and enhances the inflammatory response. PAR2 deficiency protected mice during IAV infection. However, the PAR2 expressing cell-types contributing to IAV pathology in mice and the mechanism by which PAR2 contributes to IAV infection is unknown. Methods: IAV infection was analyzed in global (Par2-/-), myeloid (Par2fl/fl;LysMCre+) and lung epithelial cell (EpC) Par2 deficient (Par2fl/fl;SPCCre+) mice and their respective controls (Par2+/+ and Par2fl/fl). In addition, the effect of PAR2 activation on polyinosinic-polycytidylic acid (poly I:C) activation of TLR3 was analyzed in bone marrow-derived macrophages (BMDM). Lastly, we determined the effect of PAR2 inhibition in wild-type (WT) mice. Results: After IAV infection, Par2-/- and mice with myeloid Par2 deficiency exhibited increased survival compared to infected controls. The improved survival was associated with reduced proinflammatory mediators and reduced cellular infiltration in bronchoalveolar lavage fluid (BALF) of Par2-/- and Par2fl/fl;LysMCre+ 3 days post infection (dpi) compared to infected control mice. Interestingly, Par2fl/fl;SPCCre+ mice showed no survival benefit compared to Par2fl/fl. In vitro studies showed that Par2-/- BMDM produced less IL6 and IL12p40 than Par2+/+ BMDM after poly I:C stimulation. In addition, activation of PAR2 on Par2+/+ BMDM increased poly I:C induction of IL6 and IL12p40 compared to poly I:C stimulation alone. Importantly, PAR2 inhibition prior to IAV infection protect WT mice. Conclusion: Global Par2 or myeloid cell but not lung EpC Par2 deficiency was associated with reduced BALF inflammatory markers and reduced IAV-induced mortality. Our study suggests that PAR2 may be a therapeutic target to reduce IAV pathology.